The effect of cigarette smoke extract and e-cigarette vape extract on extracellular vesicle production by human immune cells - Gomez, Nancy (2024)
Background: Chronic Obstructive Pulmonary Disease (COPD) is a common inflammatory airway disease, affecting the airways, lung parenchyma and vasculature, and is characterized by irreversible airflow limitation. Cigarette smoking is a significant risk factor associated with various diseases, including COPD, cardiovascular disease and cancers. E-cigarettes are promoted as a safer alternative to cigarettes and are being used as substitutes to quit cigarette smoking to reduce risk to health. Extracellular vesicles (EVs) are important intercellular communication mediators released by cells into the extracellular environment, with the capacity to transfer biological signals and information between cells and as such, influence the recipient cell function. Both cigarette smoke and e-cigarettes have been linked to increased release of EVs from a number of cellular sources. Therefore, the aim of this thesis was to investigate the effect of cigarette smoke extract (CSE) and e-cigarette vapour extract (ECVE) on the production of EVs by cells of the immune system.